Personalism of Nikolay Berdyaev’s Philosophy and French Personalism - Pavlov, Valeriy (My University, 2013)
The article examines the impact of philosophical doctrine Berdyaev on the formation and development of the French philosophy of personalism. Particular attention is paid to finding similarities and differences in the interpretation of their ideas personalistic character. Досліджується вплив філософського вчення М. Бердяєва на становлення і розвиток філософії французького персоналізму. Особлива увага приділяється пошуку спільного і відмінного в інтерпретації ними ідей персоналістичного характеру.
Keywords: God; freedom; personalism; identity; Бог; свобода; персоналізм; особистість; кафедра гуманітарних дисциплін